Dakwah Dan Isu Lesbian, Gay, Biseksual Dan Transgender (LGBT) - Faridah Faridah; Rahma Melati Amir; Nurjannah Nurjannah (STAI Bumi Silampari, 2023)
Lesbian, Gay, Bisexual and Transgender (LGBT) is a form of sexual deviation or dysfunction with a description of the definition of each item which includes the definition lesbian is defined as a term used to indicate that a woman has a sexual orientation among women, Gay is a term used to indicate that a person has same-sex relations or Same Sex Attraction, Bisexual is defined as a term used to indicate that a person has bisexual orientation, namely dual attraction at the same time both to the same sex and to the opposite sex. Transgender is a term used to indicate that a person has the desire to appear opposite of the sex he has whether he has a heterosexual, bisexual, gay or asexual social identity. The phenomenon of these cases, is behavior that is considered deviant, both in the Islamic religious and social dimensions. This became a concern in the community, In dealing with issues related LGBT groups, the role of the preacher is very important to prove that Islam is able and permissible to solve various social problems. This study uses the Library research method,collect and analyze data sources to be processed and presented in the form of a Library Research report.